Values of Tolerance Education Q.S Al-Hujurat Verse 13 Maudhu'i Studies in Tafsir Ibnu Katsir - Wulandari, Tanti; Hadinata, Arie Bastian (Lembaga Riset Mutiara Akbar, 2025)
This article analyzes the values ??of tolerance education in Surah Al-Hujurat verse 13 based on Ibn Kathir's interpretation. The verse contains the principles of equality, brotherhood, and respect for diversity, which are very relevant in building a peaceful society amidst cultural and religious plurality. This study uses a qualitative approach through literature study with the thematic interpretation method (maudhu'i). The results of the study show three main values ??in this verse: recognition of diversity as the wisdom of Allah, the importance of social harmony, and an emphasis on moral-spiritual over ethnic identity. These values ??are very relevant in education to instill an attitude of mutual respect and peaceful coexistence. This study emphasizes that the integration of Islamic teachings into everyday life can be a solution to global challenges such as discrimination and social conflict. Thus, Surah Al-Hujurat verse 13 becomes a strong ethical foundation in instilling the values ??of tolerance both in local and global contexts.